Features of the course of the postoperative period and pathomorphological changes of organs in patients with COVID-19 surgical profile - D. V. Zaitsev; S. N. Styazhkina; N. A. Kiryanov; A. K. Akhmetshina; R. R. Yakupov; I. A. Osipova; Yu. P. Kamasheva; O. A. Ishkildina; A. R. Fakhrtdinova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Frequent development SARS-CoV-2 in patients with a surgical profile of a planned and emergency order indicate the need to study the features of the course of the postoperative period and histological examination of autopsy material of lung tissues in patients with coronavirus infection in these individuals.